2019
DOI: 10.1039/c9nr02477h
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of cysteine assembly on Au(100): electrochemistry, in situ STM and molecular modeling

Abstract: Unique two-dimensional super-structures form when cysteine self-assembles on single-crystal Au(100) due to inter-molecular forces and adsorption energetics, addressed through a comprehensive experimental and quantum computational approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…The release of molecular hydrogen has not been experimentally confirmed . Abraham et al assumed that the physisorption occurs at room temperature, while chemisorption is possible at high temperatures, which is also supported by theoretical evidence of Engelbrekt et al Some studies that explored cystine binding to metals claimed both CYS and cystine bind in the same way, as thiolates. , Watanabe et al observed by surface-enhanced Raman scattering (SERS) that adsorbed cystine exists in an equilibrium with cysteine-thiolate, i.e., the breaking of the disulfide bond may follow adsorption. Cystines can chemisorb after disulfide bond breaking or physisorb without breaking. , The creation and adsorption of thiolates is likelier for longer incubation times, suggesting breaking of the disulfide bond and the adsorption of thiolates is thermodynamically more favorable, but kinetically impaired .…”
Section: Resultsmentioning
confidence: 70%
“…The release of molecular hydrogen has not been experimentally confirmed . Abraham et al assumed that the physisorption occurs at room temperature, while chemisorption is possible at high temperatures, which is also supported by theoretical evidence of Engelbrekt et al Some studies that explored cystine binding to metals claimed both CYS and cystine bind in the same way, as thiolates. , Watanabe et al observed by surface-enhanced Raman scattering (SERS) that adsorbed cystine exists in an equilibrium with cysteine-thiolate, i.e., the breaking of the disulfide bond may follow adsorption. Cystines can chemisorb after disulfide bond breaking or physisorb without breaking. , The creation and adsorption of thiolates is likelier for longer incubation times, suggesting breaking of the disulfide bond and the adsorption of thiolates is thermodynamically more favorable, but kinetically impaired .…”
Section: Resultsmentioning
confidence: 70%
“…A bias voltage is applied across the metal support and the extremely sharp STM probe, generating tunneling currents, which are transformed to high-resolution conductivity images when the STM tip is scanned across the SAM-modified metal support. Zhang and associates have reported extensive in situ STM investigations using a wide range of alkanethiols on single-crystal gold [6,[64][65][66]. In situ STM combined with electrochemical control can also directly map real-time SAM dynamics and structural features.…”
Section: Microscopymentioning
confidence: 99%
“…Since their first description, 1 thiol self-assembled monolayers (SAM) on gold surfaces and nanoparticles have been widely used in a variety of technological applications, [2][3][4][5][6][7][8][9][10][11][12][13] and studied with a wealth of diffraction, [14][15][16][17][18] spectroscopic 8,[19][20][21][22][23] and other surface science techniques. 24 In addition, thiol SAMs have been modeled theoretically by several ab initio (mainly density functional theory, DFT) [25][26][27][28][29][30][31][32] and molecular mechanics 27,28,[33][34][35][36][37][38] studies.…”
Section: Introductionmentioning
confidence: 99%